2010
DOI: 10.1007/s00709-010-0221-x
|View full text |Cite
|
Sign up to set email alerts
|

Megasporogenesis and programmed cell death in Tillandsia (Bromeliaceae)

Abstract: The degeneration of three of four meiotic products is a very common process in the female gender of oogamous eukaryotes. In Tillandsia (and many other angiosperms), the surviving megaspore has a callose-free wall in chalazal position while the other three megaspores are completely embedded in callose. Therefore, nutrients and signals can reach more easily the functional megaspore from the nucellus through the chalazal pole with respect to the other megaspores. The abortion of three of four megaspores was alrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 56 publications
2
30
2
3
Order By: Relevance
“…The many ribosomes, both free and associated within the ER, are likely involved in producing lytic enzymes. The dead cells often showed traces of partially lysed, osmiophilic cytoplasm and nuclei, hallmarks of PCD in plants (Brighigna et al, 2006;Papini et al, 1999Papini et al, , 2010cPapini et al, , 2011. At maturity, these dead cells are characterized by their walls, which possess a loose and filamentous matrix.…”
Section: Superficial and Spongy Tissuesmentioning
confidence: 99%
“…The many ribosomes, both free and associated within the ER, are likely involved in producing lytic enzymes. The dead cells often showed traces of partially lysed, osmiophilic cytoplasm and nuclei, hallmarks of PCD in plants (Brighigna et al, 2006;Papini et al, 1999Papini et al, , 2010cPapini et al, , 2011. At maturity, these dead cells are characterized by their walls, which possess a loose and filamentous matrix.…”
Section: Superficial and Spongy Tissuesmentioning
confidence: 99%
“…Later on these plastids fully degenerate and are hardly recognizable. 48,67 Plastids in tapetum cells of Lobivia rauschii show several concentric double-membrane structures, and many electron-dense plastoglobules. 67 No vesicles leaving the organelle and no role of autophagy have as yet been described during the degradation of these types of plastids.…”
Section: Autophagy During Internal Degradation Of Chloroplasts and Otmentioning
confidence: 99%
“…They are bound by a membrane and contain many membranes, usually in concentric circles ( Fig. 10 in Papini et al 48 ). These bodies are often present at the interface of cytoplasm and vacuole, whereby they can protrude far into the vacuole.…”
Section: Microautophagymentioning
confidence: 99%
“…9 In the females of oogamous eukaryotes, the megasporocyte develops into a functional megaspore with a callose-free wall in the chalazal position while the other 3 megaspores are surrounded by a callose layer; which of the 4 megaspores will develop into functional megaspores or supernumerary megaspores seems to be associated with callose deposition around the tetrad. 10 A study of dandelion ovules revealed the deposition of callose in both diplosporous and sexual dandelions; however, callose deposition was noted mostly at the micropylar pole of the megasporocyte in a diplosporous dandelion, and it was suggested to be correlated with abnormal asynaptic meiosis. 11 Despite these findings, knowledge of the role of callose deposition in embryo sac development is limited.…”
Section: Introductionmentioning
confidence: 99%